Influence of seamless nursing model of humanistic care on nursing quality and blood infection risk of neurosurgical ICU patients and its correlation with APACHE II score - Liu, Fuhua; Wang, Xiaoting (Frontiers in Public Health, 2022)
This research aims to explore the influence of seamless nursing mode of humanistic care on nursing quality and blood infection risk of ICU patients in neurosurgery, and the model of correlation with APACHE II score. 110 ICU patients are grouped into control set and study set, which are, respectively, given the previous routine nursing and the seamless management based on humanistic care to compare the two sets in the following aspects: nursing quality, blood infection rate, anxiety and depression extension before and after nursing, nursing satisfaction and APACHE II score, and to figure out the correlation between patient nursing quality score, and to compare blood infection and APACHE II score. Comparison and statistical analysis are used to disclose the influence and the correlation. The results show that there is not only a large negative correlation between nursing quality scores and APACHE II scores, but also a large negative correlation between the risk of blood infection and APACHE II score.